2020
DOI: 10.3390/ijerph17165693
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health Consciousness and Home-Based Exercise in China during the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, people have reduced the frequency of going out, and need to engage in health behaviors at home. Home-based exercise has aroused people’s attention. This paper aims to examine the influencing mechanism of health consciousness on home-based exercise during the COVID-19 pandemic. A questionnaire method was used to select 449 Chinese respondents on an online platform; the questionnaire includes a health consciousness scale, health life goal scale, perceived behavioral control scale, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 74 publications
4
51
2
Order By: Relevance
“…Health consciousness behavior and attitude play a significant role in the formation of a healthy lifestyle. A study conducted in China that explores the relationship between health consciousness and home-based exercise during the COVID-19 pandemic reported similar results as mentioned above ( Pu et al, 2020 ). A significant driver of home-based exercise is health consciousness.…”
Section: Discussionsupporting
confidence: 70%
“…Health consciousness behavior and attitude play a significant role in the formation of a healthy lifestyle. A study conducted in China that explores the relationship between health consciousness and home-based exercise during the COVID-19 pandemic reported similar results as mentioned above ( Pu et al, 2020 ). A significant driver of home-based exercise is health consciousness.…”
Section: Discussionsupporting
confidence: 70%
“…We further found that participants who regularly underwent health checkups tended to have lower social participations with respect to meeting others, which could be a result of health consciousness regarding the risk of COVID-19. Health-conscious people can be sensitive to the COVID-19 pandemic and have their own home-based health control methods, which may lead to their reduced social participation [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an approach that emphasizes the positive benefits of behavior would be a useful intervention in the self-determined motivation of physical activity during the COVID-19 situation. In particular, it was found that the ATT toward physical activity, which is based on health consciousness during the pandemic, could play a significant role in a healthy lifestyle, including regular physical activity (Pu et al, 2020 ; Sang et al, 2020 ). The search and identification of the practical values that constitute such an attitude remain the main tasks of a follow-up study.…”
Section: Discussionmentioning
confidence: 99%